2008
DOI: 10.1186/ar2362
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to mutated citrullinated vimentin and disease activity score in early arthritis: a cohort study

Abstract: Introduction The aim of our study was to investigate the association between arthritic disease activity and antibodies to mutated citrullinated vimentin (anti-MCV), because such a relation has been suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
3
3

Year Published

2009
2009
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 19 publications
6
50
3
3
Order By: Relevance
“…It was observed that anti-MCV autoantibodies had the highest AUC value (0.920) compared with anti-CCP and RF antibodies for RA patients since the area under a ROC curve (AUC) quantifies the overall ability of the test to discriminate between those individuals with the disease and those without the disease. In our study, specificity and sensitivity values of anti-MCV for the established RA were most comparable to the findings of Ursum et al [18]. Sahin et al [19] demonstrated that the sensitivity and specificity of anti-MCV vary in the literature between 49 and 74 % up to 79 and 96 %, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…It was observed that anti-MCV autoantibodies had the highest AUC value (0.920) compared with anti-CCP and RF antibodies for RA patients since the area under a ROC curve (AUC) quantifies the overall ability of the test to discriminate between those individuals with the disease and those without the disease. In our study, specificity and sensitivity values of anti-MCV for the established RA were most comparable to the findings of Ursum et al [18]. Sahin et al [19] demonstrated that the sensitivity and specificity of anti-MCV vary in the literature between 49 and 74 % up to 79 and 96 %, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…However, since no correlation coefficient was given in their study, the strength of the correlation is unknown. In a study performed on adult patients with early arthritis, Ursum et al (16) found very low correlation between anti-MCV concentrations and CRP, ESR and swollen joint count at baseline and at 1 and 2 years of follow-up. However, anti-MCV antibodies were associated with more severe RA disease, as measured by disease activity score (DAS) 28, ESR, and swollen joint count over time.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, a human recombinant mutated isoform of vimentin, citrullinated in vitro, was used in a new commercial enzyme-linked immunosorbent assay (ELISA) for detection of the respective antibodies against mutated citrullinated vimentin (anti-MCV) (12). Studies that compared the diagnostic accuracy of anti-MCV and anti-CCP antibodies in RA found comparable sensitivities, while the specificities were higher for anti-CCP in most cases (13)(14)(15)(16)(17)(18)(19). In contrast to RA, the occurrence of antibodies targeting citrullinated proteins, especially anti-MCV antibodies in rheumatic diseases of childhood, has remained largely unknown (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…The objective is to develop methods with sensitivity and specifi city for earlier RA diagnosis, more reliable activity markers, and prognostic indicators. Some of the autoantibodies used in RA investigation are as follows: mutated citrullinated vimentin antibodies (anti-MCV); [49][50][51] antikeratin antibodies (AKA); anti-perinuclear factor (APF); 52 antifi laggrin autoantibodies; 53 anti-human citrullinated fi brinogen antibodies (ACF); 54 anti-heterogeneous nuclear ribonucleoprotein A2 autoantibody (anti-RA33); 52 anti-interleukin 1 antibody (anti-IL1); 55 anti-alpha-enolase antibody; 56 and anti-advanced glycation end-products antibody. 57 These antibodies have, in general, good specifi city, but sensitivity lower than that of anti-CCP for diagnosing RA.…”
Section: Other Antibodiesmentioning
confidence: 99%